2022
DOI: 10.3390/ijerph19095389
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality (VR) Technology for Treatment of Mental Health Problems during COVID-19: A Systematic Review

Abstract: There was a surge in psychological distress and emotional burnout during the COVID-19 pandemic. Virtual reality (VR) is helpful as a psychological intervention whilst maintaining physical or social distancing. The present systematic review assessed the role of VR as a psychological intervention tool for mental health problems during the COVID-19 pandemic. We conducted a systematic review that followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. This study used th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
(63 reference statements)
1
18
0
Order By: Relevance
“…Virtual reality (VR) technology provides a good "roaming experience" for building users and architects, which can be applied in the process of scheme design evaluation, demonstration, and proof [10]. Integrating BIM and VR technologies to establish an efficient integration system can simulate all stages of the building and improve the application of sustainable design in the building [11]. New technology can improve the accuracy of engineering cost estimation (ECE), and technical reform is also an important part of architectural major in colleges and universities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality (VR) technology provides a good "roaming experience" for building users and architects, which can be applied in the process of scheme design evaluation, demonstration, and proof [10]. Integrating BIM and VR technologies to establish an efficient integration system can simulate all stages of the building and improve the application of sustainable design in the building [11]. New technology can improve the accuracy of engineering cost estimation (ECE), and technical reform is also an important part of architectural major in colleges and universities [12].…”
Section: Introductionmentioning
confidence: 99%
“…After the second screening, if the two independent researchers disagreed on the results, the three experts discussed and reached a consensus. Consequently, 18 papers were included in this study [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The paper's content was compiled by M.Y.…”
Section: Eligibility and Inclusionmentioning
confidence: 99%
“…The distribution of psychotherapies and psychological support was as follows: humanistic psychological support (n = 3, 17%) [16][17][18], virtual reality therapy (n = 2, 11%) [20,26],…”
Section: Types Of Psychotherapies and Psychological Supportmentioning
confidence: 99%
“…Despite the growing importance and necessity of distant-delivered treatment or non-directive treatment for psychiatric problems in this pandemic era, there has not been much research related to VR interventions for COVID-19-related psychological distress [ 35 ]. Although various studies have found that VR-based therapies could be beneficial for various mental health disorders, there has been a paucity of information on whether beneficial effect of VR-based intervention could be generalized into patients and medical staff with COVID-19-related mental-health problems [ 36 ]. To the best of our knowledge, one systematic review study [ 36 ] conducted a systematic review of VR technology for the treatment of mental health problems during COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…35 Although various studies have found that VR-based therapies could be beneficial for various mental health disorders, there has been a paucity of information on whether beneficial effect of VR-based intervention could be generalized into patients and medical staff with COVID-19-related mental-health problems. 36 To the best of our knowledge, one systematic review study 36 conducted a systematic review of VR technology for the treatment of mental health problems during COVID-19. Despite the thoroughness of the findings of the first systematic review, Hatta et al 18 had limitations in the selection bias and heterogeneity of the included studies.…”
mentioning
confidence: 99%